Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, dan Luas Wilayah terhadap Belanja Modal dengan Pertumbuhan Ekonomi sebagai Variabel Moderasi - Zahra, Hanifah; Fitra, Halkadri (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to examine the effect of local income, general allocation funds, and regional size on capital expenditure, with economic growth as a moderating variable, in local governments in Sumatra during the 2021–2023 period. This research uses a quantitative approach. Samples were selected using a purposive sampling technique with a total of 246 local governments in Sumatra during the 2021–2023 period. Data were analyzed using Moderated Regression Analysis (MRA) with EViews 13. Based on the analysis result, it was concluded that local income, general allocation funds, and regional size had a positive and significant effect on capital expenditure. This means that higher local income, increased general allocation funds, and larger regional size increase both the need for and the capacity to allocate capital expenditure. However, economic growth was unable to moderate the relationship between local income, general allocation funds, and regional size on capital expenditure.